2006
DOI: 10.1002/ts.181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β‐xylanase supplementation of boiled castor seed meal‐based diets on the performance, nutrient absorbability and some blood constituents of pullet chicks

Abstract: β‐xylanase addition improved apparent nitrogen and fibre absorption as well as feed transit time. Up to 150 g kg−1 boiled castor seed meal could be incorporated into pullet chick diets without any adverse effect on growth performance or blood constituents. Copyright © 2006 John Wiley & Sons, Ltd

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…The marginal improvement found with the fermented cake + enzyme may be attributed to the combination of fermentation process and enzyme degradation of the fibre that made nutrients available to the birds. This is in agreement with Babalola et al [7] who reported improved nutrient availability to pullet chicks fed β-xylanase supplemented castor seed meal diet.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The marginal improvement found with the fermented cake + enzyme may be attributed to the combination of fermentation process and enzyme degradation of the fibre that made nutrients available to the birds. This is in agreement with Babalola et al [7] who reported improved nutrient availability to pullet chicks fed β-xylanase supplemented castor seed meal diet.…”
Section: Resultssupporting
confidence: 93%
“…There is another problem as the cake contains a high level of fibre, perhaps 23% because undelinted seeds are used in the processing [5]. This high fibre content has limited the extent to which it can be used in the diets of poultry which lack the appropriate enzymes capable of degrading fibre [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…1 The use of antibiotics as growth promoters and for prevention and treatment of diseases has become commonplace as poultry producers have adopted intensive farming systems. However, there is growing concern regarding the possible build-up of antibiotic residues in animal products, which can be harmful to consumers, and the development of drug-resistant bacteria, attributed to continuous feeding of antibiotics at sub-therapeutic levels.…”
Section: Introductionmentioning
confidence: 99%
“…To confirm this assumption, we conducted an experiment to examine the effect of A. awamori on growth performance, digestibility and skeletal muscle protein metabolism in broilers. Many antibiotics have been used to promote animal health and to improve utilization of nutrients and growth performance in poultry (Babalola et al . 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To confirm this assumption, we conducted an experiment to examine the effect of A. awamori on growth performance, digestibility and skeletal muscle protein metabolism in broilers. Many antibiotics have been used to promote animal health and to improve utilization of nutrients and growth performance in poultry (Babalola et al 2006). However, there is strong public and governmental concern about the increasing prevalence of resistance to antibiotics in disease-causing bacteria because many antibiotics now available to treat human diseases will become ineffective in the future (Casewell et al 2003).…”
Section: Introductionmentioning
confidence: 99%